The estimation of ES in the environment, created by pulsed source of noise - Сахацкий, В.Д.; Гладуш, В.А. (Eastern-European Journal of Enterprise Technologies, 2012)
Distribution of intensity of an electromagnetic field over terrestrial surface near to a pulsed source of radiations is investigated at various moistness of soil.